The Influence of the Leadership in Technical and Vocational Education - Nashir, Irdayanti Mat; Mustapha, Ramlee; Yusoff, Abdullah (ASPENSI, 2015)
ABSTRACT: Leadership in general is a process to influences the human activities, which has connection with what they need to do to achieve the organisationâs objectives. Meanwhile, leadership research has taken different perspectives: leader traits, behaviours, and the influences of situational characteristics on leader effectiveness, for example, have all been studied. This study was performed to obtain the relationship between the elements of leadership among administrators at the polytechnic in Malaysia. A total of 102 administrators who have been involved in this study. Data were collected using a set of instruments to measure the elements of leadership. Data were analyzed using the SPSS (Statistical Package for the Social Sciences) 21. The findings of the analysis of structural equation indicates that Strategic Thinking, Vision and Mission, Rewards, Personality, and Innovative Thinking have had significantly high correlation between each other. The findings show also that the elements of Strategic Thinking and Rewards influenced in developing the Vision and Mission of the TVE (Technical and Vocational Education). In addition, the Personality has also a significant relationship with the elements of Rewards and Innovative Thinking. As a leader in TVE institutions, it is necessary for the leaders to practice the effective leadership style as well as the realization of education and training systems in line with industry requirements and the current market.KEY WORD: Technical and vocational education, structural equation modelling, strategic thinking, vision and mission, rewards, personality, and innovative thinking.RINGKASAN: âPengaruh Kepimpinan dalam Pendidikan Teknik dan Vokasionalâ. Kepimpinan secara amnya adalah satu proses untuk mempengaruhi kegiatan manusia, yang mempunyai kaitan dengan apa yang mereka perlu lakukan untuk mencapai matlamat organisasi. Sementara itu, penyelidikan kepimpinan telah mengambil perspektif yang berbeza: ciri-ciri pemimpin, tingkah-laku, dan pengaruh ciri-ciri situasi pada keberkesanan mengenai pemimpin, sebagai contoh, semuanya telah dikaji. Kajian ini dilaksanakan untuk mendapatkan hubungan di antara elemen-elemen kepimpinan dalam kalangan pentadbir di politeknik Malaysia. Sejumlah 102 orang pentadbir telah terlibat dalam kajian ini. Data telah dikumpulkan menggunakan satu set instrumen untuk mengukur elemen kepimpinan tersebut. Data telah dianalisis menggunakan perisian SPSS 21. Hasil analisis persamaan struktur menunjukkan bahwa Pemikiran Strategik, Visi dan Misi, Ganjaran, Personaliti, dan Pemikiran Inovatif mempunyai korelasi signifikan yang tinggi antara satu sama lain. Dapatan kajian juga menunjukan bahawa unsur Pemikiran Strategik dan Ganjaran mempengaruhi dalam membangunkan Visi dan Misi PTV (Pendidikan Teknik dan Vokasional). Di samping itu, Personaliti juga mempunyai hubungan yang signifikan dengan unsur Ganjaran dan Pemikiran Inovatif. Sebagai pemimpin dalam institusi PTV, adalah perlu bagi para pemimpin untuk mengamalkan gaya kepimpinan yang berkesan dan juga merealisasikan sistem pendidikan dan latihan selaras dengan keperluan industri dan pasaran semasa.KATA KUNCI: Pendidikan teknikal dan vokasional, persamaan permodelan struktural, pemikiran strategik, visi dan misi, ganjaran, personaliti, dan pemikiran inovatif.Â Â Â Â About the Authors: Irdayanti Mat Nashir and Prof. Dr. Ramlee Mustapha are the Lecturers at the Faculty of Technical and Vocational Education UPSI (Sultan Idris University of Education) in Tanjong Malim, Perak, Malaysia. Abdullah Yusoff is a Lecturer at the Polytechnics of Sultan Azlan Shah in Tanjong Malim, Perak, Malaysia. Corresponding author is: irdayantis@yahoo.comHow to cite this article? Mat Nashir, Irdayanti, Ramlee Mustapha & Abdullah Yusoff. (2015). âThe Influence of the Leadership in Technical and Vocational Educationâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(1) June, pp.77-84. Bandung, Indonesia: Minda Masagi Press and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (March 24, 2015); Revised (May 24, 2015); and Published (June 30, 2015).